Solidification structure and high temperature oxidation resistance of nano titanium dioxide TiO2 added Inconel 718 deposits by arc melt. (1st May 2022) - Chen, Cuixin; Li, Xinhang; Liu, Baoxi; Zuo, Yuqiang; Liu, Kailun; Guo, Weibing; Xue, Haitao; Yin, Fuxing
Abstract: In order to refine the microstructure of Inconel 718 and achieve high performance, nanometer TiO2 particles (nano-TiO2 ) were adopted to modify the solidification structure. After pretreating nano-TiO2, oxide added 718 nickel alloy were prepared by using arc melting technology, and the microstructure and oxidation behavior were investigated in detail. The results show that the microstructures of Inconel 718 alloys with different content of nano-TiO2 are all dendritic-like, and the size of dendrite gradually decreases and the shape tends to become equiaxed grain with the increase of TiO2 content. The grain refinement effect is best for 0.6%TiO2 added alloy. The precipitated phases become finer and more uniform due to grain refinement. The high temperature oxidation experiments of Inconel 718 alloy with different volume fractions of TiO2 show that the main oxides are Cr2 O3, accompanying with some Nb-Fe oxides. With the decrease of grain size, the size of oxides gradually decreases, and the oxidation layers are more and more compact, which effectively improves the oxidation resistance.